Surgical Technique to Bring Down the Patellar Height and to Reconstruct the Tendon for Chronic Patellar Tendon Rupture - Harato, Kengo (Arthrosc Tech, 2017)
Although surgical treatment is the gold standard for chronic patellar tendon rupture, the technique of patellar tendon reconstruction is still difficult. Basically, good clinical results of surgical repair for acute patellar tendon rupture have been reported. However, the results of reconstructive surgery for chronic patellar tendon rupture are still inconsistent. Some surgical options have been previously reported. For example, surgeons need to choose between 1- and 2-stage reconstruction. Furthermore, contralateral bone-tendon-bone graft, ipsilateral semitendinosus tendon graft, Achilles tendon allograft, and an artificial ligament have been used to reconstruct the patellar tendon. Generally, surgeons are concerned about postoperative complications, including loss of knee flexion, quadriceps weakness, and wound problems. One of the key points to avoid these complications is to improve proximal patellar migration. The purpose of this article is to present an easy and safe technique to bring down the patellar height with polyethylene tape and to reconstruct the patellar tendon with an artificial ligament. Although it has limitations, the described technique can facilitate reconstruction of chronic patellar tendon rupture.